Greenhouse gas emissions from urban ponds are driven by nutrient status and hydrology. Issue 3 (12th March 2019) - Peacock, Mike; Audet, Joachim; Jordan, Sabine; Smeds, Jacob; Wallin, Marcus B.
Abstract: Inland waters emit significant quantities of greenhouse gases (GHGs) such as methane (CH4 ) and carbon dioxide (CO2 ) to the atmosphere. On a global scale, these emissions are large enough that their contribution to climate change is now recognized by the Intergovernmental Panel on Climate Change. Much of the past focus on GHG emissions from inland waters has focused on lakes, reservoirs, and rivers, and the role of small, artificial waterbodies such as ponds has been overlooked. To investigate the spatial variation in GHG fluxes from artificial ponds, we conducted a synoptic survey of forty urban ponds in a Swedish city. We measured dissolved concentrations of CH4 and CO2, and made complementary measurements of water chemistry. We found that CH4 concentrations were greatest in high‐nutrient ponds (measured as total phosphorus and total organic carbon). For CO2, higher concentrations were associated with silicon and calcium, suggesting that groundwater inputs lead to elevated CO2 . When converted to diffusive GHG fluxes, mean emissions were 30.3 mg CH4 ·m −2 ·d −1 and 752 mg CO2 ·m −2 ·d −1 . Although these fluxes are moderately high on an areal basis, upscaling them to all Swedish urban ponds gives an emission of 8336 t CO2 eq/yr (±1689) equivalent to 0.1% of Swedish agricultural GHG emissions. Artificial ponds could be important GHG sources in countries with larger proportions of urban land.